Desenvolvimento de um conversor estático PWM para o acionamento de LED’S para iluminação publica - Lopes, Felipe Simões [UNESP] (2015)
This work deals with the development of a switched-mode power supply circuit based on a Buck topology converter with a Boost Rectifier One-Cycle Control with Power Factor Correction developing, thus, a source of direct current for a module of 50 power LEDs that will be used in a lamp for public street lightning. It is presented, at first, some aspects about the most common technologies used in lamps of public street lightning in Brazil and a comparison with the White LED high power, which is the one that presents itself as the most promising among the existing market. Then it is presented the detailed development of the static converter switched PWM, consisting of a Boost rectifier with power factor correction and methodology of control One-Cycle Control associated with a Buck converter controlled by a PI method that operates as a direct current source . At the end of the simulation results of the circuit through the PSIM software are presented to verify the design behavior